Effects of Context and Genuineness in the Experience of Art. (July 2019) - Grüner, Susanne; Specker, Eva; Leder, Helmut
Studies found that genuine artworks viewed in a museum receive higher appreciation ratings than reproductions in the laboratory. Due to the mutual variation of context and genuineness, these studies were not able to disentangle these factors. A study designed by Brieber, Leder, and Nadal to systematically differentiate between these two variables did not find an effect of context or genuineness. To substantiate these results, we setup a conceptual replication by using the same 2 (museum/laboratory) by 2 (genuine/reproduction) between-subjects design with improved manipulations of context and genuineness. We found an effect of context, as artworks presented in a museum were liked more and rated more interesting than in the laboratory. We did not find effects of genuineness. Exploratively, we found that art style had a big impact on how artworks were rated regardless of context and genuineness, indicating that this may be a more important factor for aesthetic experience.